2001
DOI: 10.1007/s11627-001-0132-9
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and micrografting of lentil shoots

Abstract: A protocol for regeneration and micrografting of shoots of lentil (Lens culinaris Medik) was developed. Multiple shoots (4-5) were regenerated from cotyledonary node explants on Murashige and Skoog (MS) medium containing 8.8 mM 6-benzylaminopurine. In vitro regenerated shoots were micrografted on rootstocks with 96% efficiency. The successful grafts were transplanted to pots in Redi-earth TM , hardened off and were grown to maturity with 100% success. The success of the micrografting was independent of the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…AAA, and Uniola paniculata, (Bairu et al 2007(Bairu et al , 2008Valero-Aracama et al 2010) Conventional method for in vitro propagation such as micrografting appears to be a promising means in regenerating in vitro shoots. Grafting has been successfully used in the regeneration protocol for many species that are otherwise difficult to root in vitro, including Lens culinaris, Persea americana, Phaseolus polyanthus, and Lathyrus sativus (Gulati et al 2001;Raharjo and Litz 2004;Zambre et al 2001Zambre et al , 2002. In this study, preliminary experiments using elongated shoots grafted onto rootstock of B. sinuspersici cuttings suggested grafting as a promising option for increasing the efficiency of the regeneration procedure because many of the grafted plants remained viable for over a month (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…AAA, and Uniola paniculata, (Bairu et al 2007(Bairu et al , 2008Valero-Aracama et al 2010) Conventional method for in vitro propagation such as micrografting appears to be a promising means in regenerating in vitro shoots. Grafting has been successfully used in the regeneration protocol for many species that are otherwise difficult to root in vitro, including Lens culinaris, Persea americana, Phaseolus polyanthus, and Lathyrus sativus (Gulati et al 2001;Raharjo and Litz 2004;Zambre et al 2001Zambre et al , 2002. In this study, preliminary experiments using elongated shoots grafted onto rootstock of B. sinuspersici cuttings suggested grafting as a promising option for increasing the efficiency of the regeneration procedure because many of the grafted plants remained viable for over a month (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…However, micrografting was more effective for sunflower plant recovery from regenerated shoots, as the graft survival was much higher than the rooting efficiency, regardless of the regeneration regime (Table 3). Micrografting was used to recover regenerated shoots of citrus (Citrus sinensis; Peña et al 1995a, b), cotton (Gossypium hirsutum; Luo and Gould 1999), lentil (Lens culinaris; Gulati et al 2001), and king protea (Protea cynaroides; Wu et al 2007), in which rooting was also problematic. Shoots from sunflower leaf tissues were also successfully micrografted to form whole plants (Zhang and Finer 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Higher numbers of graft plants are possible because they establish from scions with one internode, whereas the successful rooting requires at least two nodes (one node for rooting). Under ideal conditions, up to five grafts could be made from a donor plant (three was more (Gulati et al 2001) compared to rooted cutting methods that can take 6 wk (Polanco and Ruizz 1977).…”
Section: Comparison Of Rooted Cutting Vs Graftingmentioning
confidence: 99%
“…In our preliminary studies with common bean, we consistently observed that rooting of cuttings took more time than graft establishment. Rooting problems in other pulse crops such as lentil have been overcome with micrografting techniques; Gulati et al (2001) experienced 96% efficiency with this technique and reported that lentil grafts established 4 wk earlier than rooted cuttings.…”
mentioning
confidence: 99%